Micro-Doppler Effect of Extended Streamlined Targets Based on Sliding Scattering Centre Model - Tang, Bo (Společnost pro radioelektronické inženýrství, 2016)
The scattering center of extended streamlined targets can slide when the direction of radiation is changed. The sliding scattering center has influence on the micro-Doppler effect of micro-motion of the extended streamlined target. This paper focused on the micro-Doppler of the extended streamlined target for the bistatic radar. Based on the analysis, the analytical expressions of the micro-Doppler of coning motion with sliding scattering center model were given for bistatic radar. And the results were validated by the simulated results of the scattering field based on the full-wave method of the electromagnetic computation. The results showed that the sliding of the scattering center can make the micro-Doppler be less and distorted, and the influence of the sliding is different for two different types of the sliding scattering centers: sliding on the surface and sliding on the bottom circle. The analytical expressions of the micro-Doppler are helpful to analyze the time-frequency presentations (TFR) of the coning motion of the extended streamlined target and to estimate the parameters of the target.
Keywords: Micro-Doppler; sliding scattering centre; extended streamlined targets